ANALISA SISTEM INFORMASI GEOGRAFIS PEMETAAN RUMAH SAKIT DI KOTA SAMARINDA BERBASIS WEB - Novianita, Novianita (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
There have been many hospitals in Samarinda, but the rapid development of hospitals in Samarinda, not accompanied by the development of media support facilities and hospital information is still lacking especially in terms of mapping hospitals in Samarinda City. Currently, the hospital in Samarinda has 14 hospitals. To speed up and facilitate the search of data of hospitals that currently number 14 hospitals, the proposed problem is to build a web based application of Hospital Geographic Information System (GIS) in Samarinda. The research was conducted at the Samarinda City Health Office. Methods used in data collection include field studies (interviews and observations), and library studies. Data analysis was conducted qualitatively based on technological analysis, GIS data analysis, and analysis of GIS output information. The results showed that this geographic information system could display a map of Samarinda city along with the hospital information. This geographic information system can provide solutions in solving the search for the nearest specialist doctor and show the closest route to the hospital.